Three-dimensional analysis of plate panels based on differential quadrature method - Teo, Tat Ming. (2009)
The differential quadrature (DQ)method displays potential to become an accurate numerical tool for mathematical approximation. Recently the solution capability of the DQ method has been aggressively explored especially in the field of computational mechanics. In this thesis, the DQ method is employed to solve three major categories of structural mechanics problems pertaining to plate. They are namely the bending, buckling, and free vibration of plates. The three-dimensional elasticity theory is adopted for the analysis of these plate problems as there is no DQ solution of this class in the open literature. In this study, various edge and lateral surface boundary conditions, and their combinations are considered.